Perempuan Pejuang dari Bengkulu: Biografi Politik Fatmawati Soekarno (1943-1955 M) - Safitri, Rima Dwi; Musa (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract: This study discusses female heroes who broke gender boundaries and colored the history of the Indonesian nation through their participation in politics. The problems of this study are, how was Indonesia's condition towards independence? What was the background and journey of Fatmawati Soekarno as the First Lady of the Republic of Indonesia? What was Fatmawati Soekarno's contribution as the First Lady in the Indonesian political scene? This study uses a feminist sociological approach. The theories used are the theory of social roles and feminism. The research method is a historical research method with four stages, namely heuristics, verification, interpretation, and historiography. The results of this study are that Fatmawati's journey in politics began when she married Soekarno and had the status of the First Lady of the Republic of Indonesia. Fatmawati has carried out her state duties well, such as making national and international visits, entertaining state guests at the state palace who came from India, Pakistan, and other countries, and becoming an intermediary for the joining of Mrs. Wakijah Sukijo, Mrs. Pujo Utomo, and Mrs. Mahmudah Masjhud as the first three women to join the KNIP which marked a new history for women's participation in politics in Indonesia. During her time as First Lady, Fatmawati also became a companion and advisor to women's organizations such as Kowani (Indonesian Women's Congress), Perwari (Indonesian Women's Association), Persis (Army Wives Association). Fatmawati also cared deeply about the welfare of the people, especially women. This was proven by the establishment of the Ibu Soekarno Foundation which functions as a hospital for children with cancer. This foundation not only provides medical services, but also education for patients and their families so that they continue to receive a good education. Fatmawati has a strong commitment to empowering women to be economically independent and not dependent on men. Abstrak: penelitian ini membahas tentang pahlawan perempuan yang mendobrak batasan gender dan mewarnai sejarah bangsa Indonesia melalui partisipasinya di dunia politik. Permasalahan penelitian ini yaitu, bagaimana kondisi Indonesia menuju kemerdekaan? bagaimana latar belakang dan perjalanan Fatmawati Soekarno sebagai Ibu Negara pertama Republik Indonesia? apa kontribusi Fatmawati Soekarno sebagai Ibu Negara dalam panggung politik Indonesia? Penelitian ini menggunakan pendekatan sosiologi feminis. Adapun teori yang digunakan adalah teori peranan sosial dan feminisme. Metode penelitiannya adalah metode penelitian sejarah dengan empat tahapan yakni heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian ini adalah perjalanan Fatmawati di bidang politik dimulai ketika ia menikah dengan Soekarno dan berstatus sebagai Ibu Negara pertama Republik Indonesia. Fatmawati telah menjalankan tugas kenegaraan dengan baik seperti melakukan kunjungan nasional dan internasional, menjamu tamu-tamu negara di istana negara yang datang dari India, Pakistan, dan negara lainnya, dan menjadi perantara bergabungnya Ny. Wakijah Sukijo, Ny. Pujo Utomo, dan Ny. Mahmudah Masjhud sebagai tiga perempuan pertama yang tergabung dalam KNIP yang menandai sejarah baru bagi partisipasi perempuan dalam politik di Indonesia. Selama menjadi Ibu Negara Fatmawati juga menjadi pendamping sekaligus penasihat organisasi perempuan seperti Kowani (Kongres Wanita Indonesia), Perwari (Persatuan Wanita Indonesia), Persis (Persatuan Istri Tentara). Fatmawati juga sangat peduli dengan kesejahteraan rakyat, khususnya kaum perempuan. Hal ini dibuktikan dengan pendirian Yayasan Ibu Soekarno yang berfungsi sebagai rumah sakit bagi anak-anak penderita kanker. Yayasan ini tidak hanya memberikan pelayanan medis, tetapi juga pendidikan bagi pasien dan keluarganya agar tetap mendapatkan pendidikan yang baik. Fatmawati memiliki komitmen kuat untuk memberdayakan perempuan agar mandiri secara ekonomi dan tidak bergantung pada laki-laki.